PENGARUH PENGGUNAAN GAME ONLINE TERHADAP KECERDASAN EMOSIONAL REMAJA SISWA KELAS XI SMK NEGERI 2 SALATIGA - Abner Delwanni Korwin S; Tritjahjo Danny Soesilo; Maya Rahadian Septiningtyas (Bajang Institute, 2024)
The aim of this research is to determine the significance of the influence of the use of online games on the emotional intelligence of class XI adolescent students at SMK Negeri 2 Salatiga. This research is a causal comparative research with data analysis techniques using simple linear regression and an instrument in the form of a questionnaire. The results of this study indicate that there is a significant influence on online game playing behavior on students' emotional intelligence with the contribution of the online game playing behavior variable (X) to students' emotional intelligence (Y) amounting to 54.2%, the remainder (45.8%) comes from from other variables not examined in this study, then tcount is greater than ttable, namely 10.870 > 3.390 and the significance value of t is less than 0.05 (0.000 < 0.05) and significance coefficient 0.000 < 0.050.